A Novel Genospecies of Borrelia burgdorferi Sensu Lato Associated with Cricetid Rodents in Brazil - Bárbara C. Weck; Maria Carolina A. Serpa; Marcelo B. Labruna; Sebastián Muñoz-Leal (Microorganisms, 2022)
Borrelia burgdorferi sensu lato (Bbsl) spirochetes thrive in sylvatic transmission cycles infecting vertebrates and their ticks. Rodents and ticks of the genus Ixodes are important hosts of these spirochetes globally. Although evidence suggests that Borrelia burgdorferi sensu stricto does not exist in South America, genospecies of the group (Bbsl) can be found in this region but have been poorly characterized from a genetic viewpoint, and data on their ecoepidemiology are still incipient. Aiming to detect the natural foci of Borrelia in Brazil, we targeted small mammals inhabiting seven forests fragments during a period of three years (2015–2018). Organs (lung) from two Oligoryzomys rodents over a total of 382 sampled mammals were positive, and we performed a molecular characterization of 10 borrelial genes to achieve a robust analysis. Phylogenetic trees inferred from 16S rRNA, flaB, ospC, and seven MLST loci (clpA, nifS, pepX, pyrG, recG, rlpB, and uvrA) support the characterization of a novel genospecies of Bbsl that we herein name “Candidatus Borrelia paulista” Rp42. Remarkably, “Ca. B. paulista” is phylogenetically related to Borrelia carolinensis, a genospecies that infects Ixodes ticks and cricetid rodents in North America. A previous study performed in the same area identified Ixodes schulzei feeding on Oligoryzomys rodents. Although this tick species could be considered a probable host for this novel Borrelia sp., further research is needed to confirm this hypothesis.